OWNERSHIP STRUCTURE AND FINANCIAL REPORTING QUALITY IN LISTED NON-FINANCIAL FIRMS IN NIGERIA - Kurawa, Junaidu Muhammad; Alhassan, Ismail; Islam, K. M. Anwarul; Haque, Md. Shariful (International Journal of Accounting & Finance Review, 2021)
The objective of this study is to appraise the effect of the ownership structure on the quality of financial reporting in Nigeria. The study used data from 41 non-financial firms listed on the Nigerian Stock Exchange (NSE) for the 2011 to 2019 period. The Generalised Method of Moments (GMM) technique was adopted for the study which is vigorous to the threat of heteroskedasticity and endogeneity. The study findings revealed that institutional and foreign ownership has a significant negative relationship with earnings management, thereby, improving the reporting quality. However, the results show that managerial ownership has an insignificant negative relationship with earnings management. The finding of this study is also robust in scope concerning the issue of unobserved heterogeneity which prior studies have failed to address. Thus, future corporate governance reforms should recognize and sustain these efforts. The study recommends that Firms should expand their institutional and foreign ownership by providing sufficient shares to them. This is important because they frequently deploy their professionalism and wealth of experience to the firms towards meeting corporate goals and agitation of good reporting practice.  On the other hand, Firms should ensure that the shareholding of the insider managers is not too high in such a way that the proportion of their shareholding should be minimal. Their shares should not exceed 10% of the total shareholding in the company as it was found to be among the variables that reduce firms' performance.JEL Classification Codes: G32.